THE PECULIARITIES OF PSYCHOLOGICAL SERVICE IN PRE-SCHOOL EDUCATIONAL ORGANIZATIONS (Innovative Technologica: Methodical Research Journal, 2023)
The forms of organization of psychological service in preschool educational organizations and the solution of some of its tasks are described.